Cigarette Smoking Among Secondary School-Going Male Adolescents in Malaysia: Findings From the National Health and Morbidity Survey 2017. (November 2019) - Ling, Miaw Yn Jane; Rodzlan Hasani, Wan Shakira; Mohd Yusoff, Muhammad Fadhli; Abd Hamid, Hamizatul Akmal; Lim, Kuang Hock; Tee, Guat Hiong; Baharom, Nizam; Ab Majid, Nur Liana; Robert Lourdes, Tania Gayle; Mat Rifin, Halizah; Saminathan, Thamil Arasu
Smoking is a learned behavior during adolescence, and it is found predominantly among male adolescents in Malaysia. Our study aimed to investigate the prevalence and predictive factors of current cigarette smoking among school-going male adolescents in Malaysia. Data were derived from the National Health and Morbidity Survey: Adolescent Health Survey 2017, a cross-sectional study that utilized a 2-stage stratified cluster sampling to select a nationally representative sample of school-going adolescents in Malaysia (n = 27 497). Multiple logistic regression analysis was performed to identify factors associated with current cigarette smoking among male adolescents in Malaysia. Male adolescents aged 16 to 17 years (adjusted odds ratio [AOR] = 1.55; 95% confidence interval [CI] = 1.41-1.70), current illicit drug users (AOR = 8.14; 95% CI = 6.37-10.41), current alcohol users (AOR = 1.92; 95% CI = 1.65-2.23), those from rural schools (AOR = 1.60; 95% CI = 1.46-1.76), those whose parents were widowed/divorced/separated (AOR = 1.37; 95% CI = 1.21-1.55), and those whose parents/guardians were tobacco product users (AOR = 3.47; 95% CI = 2.33-5.16) were more likely to be current cigarette smokers. Tobacco control strategies should be aimed at both adolescents at risk and at promoting parental smoking cessation.